PENGARUH CAMPURAN BAHAN BAKU BIODIESEL (MINYAK KELAPA SAWIT, MINYAK JELANTAH, MINYAK LEMAK SAPI) PADA PERFORMA MESIN DIESEL 4 LANGKAH - Zufar Ali; Subagio So'im; Edi Haryono (Politeknik Perkapalan Negeri Surabaya, 2023)
The continuous use of solar, as an abiotic natural resource in all sectors, will eventually bedepleted, necessitating an alternative fuel such as biodiesel. Biodiesel is a renewable fuel commonlyderived from biological sources (vegetable and animal) and is environmentally friendly. Potentialraw materials for biodiesel include palm oil, used cooking oil, and animal fat. In this research, theseoils are converted into biodiesel through esterification and transesterification processes. Then, acombination of the three raw materials is formulated (multi-feedstock biodiesel), which will beblended with HSD (Pertamina dex) to create B20, B35, and B100 biodiesel blends. These biodieselfuels will be tested in a four-stroke diesel engine with different loads of 1000 watts, 2000 watts, and3000 watts, at various RPMs of 900, 950, 1000, and 1050, to obtain performance data such as power,torque, and fuel consumption. From the conducted tests, the characteristics of flash point, density,and viscosity of B100 biodiesel has met the biodiesel quality standards according to SNI (IndonesianNational Standard). B100 biodiesel has the highest power and torque values, while Pertamina Dexexhibits the most optimal specific fuel consumption value.